Penegakan Hukum Administrasi Dalam Perlindungan dan Pengelolaan Lingkungan Hidup di Indonesia - Samhan Nafi' BS (Universitas Ekasakti, 2024)
Environmental law enforcement aims to ensure compliance with environmental law regulations and requirements, both general and individual, through administrative, criminal, and civil law approaches. This research examines the position of administrative law enforcement in the environmental field and its development after changes in related laws. Using doctrinal legal research methods with secondary data from literature studies, the results show that administrative law enforcement plays an important role in protecting, managing, and restoring environmental quality. Its main advantage lies in its preventive nature through supervision and licensing, as well as its repressive nature through the application of administrative sanctions for violators. Changes in the law on environmental protection and management cause the licensing mechanism to change, which affects aspects of supervision and the application of administrative sanctions in administrative law enforcement in the environmental sector.